Myelomonocytic skewing in chronic myelomonocytic leukemia: phenotypic, molecular and biologic features and impact on survival. (8th March 2021) - Geissler, Klaus; Jäger, Eva; Barna, Agnes; Graf, Temeida; Graf, Elmir; Öhler, Leopold; Hoermann, Gregor; Valent, Peter
Abstract: Background: Myelomonocytic skewing is considered as a key pathophysiologic phenomenon in chronic myelomonocytic leukemia (CMML), but its prevalence and potential correlation with phenotypic, genotypic, and clinical features are poorly defined. Methods: Skewed differentiation toward the myelomonocytic over erythroid commitment as indicated by an inverse ratio of myelomonocytic/erythroid colonies was investigated in 146 patients with CMML by semisolid in vitro cultures. Results: There was a high prevalence of myelomonocytic skewing in patients with CMML (120/146, 82%); whereas, this phenomenon was rare in normal individuals (1/98, 1%). Patients with CMML with myelomonocytic skewing had higher white blood cell and peripheral blast cell counts, and lower platelet values. The number of mutations in genes of the epigenetic and/or splicing category was higher in CMML patients with as compared with patients without skewing. Patients with myelomonocytic skewing had more frequently mutations in RASopathy genes and higher growth factor independent myeloid colony formation. Interestingly, the lack of myelomonocytic skewing discriminated patients with CMML with a particularly favorable prognosis (60 vs 19 months, P  = .003) and a minimal risk of transformation. Conclusion: Myelomonocytic skewing as determined by semisolid cultures can discriminate subgroups of patients with CMML with a different phenotype, a different genotype, and a different prognosis.